The origins of Canada's feminist foreign policy. (June 2019) - Chapnick, Adam
In January 2019, a leading Canadian foreign policy blog, OpenCanada.org, declared that "[u]nder the government of Justin Trudeau, Canada has embraced a feminist foreign policy—gradually at first, and with fervor over the past year." Although critics have debated the policy's effectiveness, the embrace, if not also the fervor, was indisputable. By 2019, the Trudeau government's second foreign minister, Chrystia Freeland, was proclaiming Canada's feminist approach to international relations openly and regularly. The international community had also noticed. This article investigates the origins of the new Canadian foreign policy "brand." It finds that, contrary to popular thinking, the prime minister himself played at most a minor role in the initiation of what became a full-fledged transformation of Canada's global image.